Functional analysis of the chromo domain of HP1. - Platero, J S (1995)
Heterochromatin protein 1 (HP1) is a non-histone chromosomal protein in Drosophila with dosage-dependent effects on heterochromatin-mediated gene silencing. An evolutionarily conserved amino acid sequence in the N-terminal half of HP1 (the 'chromo domain') shares > 60% sequence identity with a motif found in the Polycomb protein, a silencer of homeotic genes. We report here that point mutations in the HP1 chromo domain abolish the ability of HP1 to promote gene silencing. We show that the HP1 chromo domain, like the Polycomb chromo domain, has chromosome binding activity, but to distinct chromosomal sites. We constructed a chimeric HP1-Polycomb protein, consisting of the chromo domain of Polycomb in the context of HP1, and show that it binds to both heterochromatin and Polycomb binding sites in polytene chromosomes. In flies expressing chimeric HP1-Polycomb protein, endogenous HP1 is mislocalized to Polycomb binding sites, and endogenous polycomb is misdirected to the heterochromatic chromocenter, suggesting that both proteins are recruited to their distinct chromosomal binding sites through protein-protein contacts. Chimeric HP1-Polycomb protein expression in transgenic flies promotes heterochromatin-mediated gene silencing, supporting the view that the chromo domain homology reflects a common mechanistic basis for homeotic and heterochromatic silencing.